A risk management tool for tackling country-wide contingent disasters: A case study on Madagascar. (October 2015) - Hochrainer-Stigler, Stefan; Mechler, Reinhard; Mochizuki, Junko
Abstract: Governments are key players in managing disaster risks, and fiscal risk management has become an integral part of disaster risk management. However, the ability of governments to implement disaster risk management strategies differs significantly across countries, depending on their capacity and resource constraints. The CatSim model and its most recent version presented in this paper helps to fill part of the information gap regarding the capacity and resources of a government to deal with natural disaster risk. We provide an in-depth example how the model works for the case of managing cyclone risk in Madagascar. In doing so, we provide recommendations as to how some of the more difficult concepts from the disaster risk theory and modelling field can be most easily understood by non-technically trained stakeholders. Such understanding is beneficial in facilitating consensus-building among various risk bearers from different sectors regarding options for managing risk. Highlights: Only publicly available model for natural disaster risk management on the country level. Used and extended based on high-level workshops in more than 22 countries. In-depth example of cyclone risk in Madagascar given.